The carbon cycle of an energy crop : Miscanthus x giganteus - Carroll, Faye (Trinity College (Dublin, Ireland). Department of Botany, 2012)
The United Nations Framework Convention on Climate Change Kyoto Protocol (1997) has driven research towards a reduction of carbon dioxide (CO2) emissions and the development of alternative energy sources. Energy crops provide the best opportunity to combine a reduction in CO2 emissions with an increase in renewable electricity generation. The conversion of surplus agricultural land to energy crops has been identified as providing the greatest potential for carbon mitigation across Europe. In Ireland Miscanthus x giganteus, a perennial rhizomatous grass from Eastern Asia, has received considerable interest as a suitable energy crop. Field trials have displayed promising yields, up to 26 t DM ha-1 yr-1, with the potential to substitute up to 37% of Ireland's gross electricity generation. However, little research has been directed towards plantbased observations and the potential of Miscanthus to mitigate carbon and reduce the greenhouse gas effect. Knowledge of the carbon cycles of bioenergy crops is critical for developing future energy policies. Fluxes of CO2 from a mature Miscanthus stand, located in Oak Park Research Centre, Co. Carlow, were measured using eddy covariance techniques and leaf and soil chambers from August 2006 to 2008.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin.